2019
DOI: 10.1111/ans.14985
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from cytoreduction and hyperthermic intraperitoneal chemotherapy for appendiceal epithelial neoplasms

Abstract: Background: Appendiceal epithelial neoplasms are rare cancers. Management of peritoneal disease from appendiceal neoplasms has historically been with debulking surgery. In recent decades, the advent of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) has become the standard of care. Here, we report our single institution 10-year experience with CRS and HIPEC for appendiceal neoplasms. Methods: This is a retrospective review from 1 January 2008 to 1 June 2017 of all patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Sugarbaker et al (8) first introduced complete cytoreductive surgery (CRS) plus heated intraoperative intraperitoneal chemotherapy (HIPEC), which provided new ideas for PMP treatment and has been suggested as the standard therapy (9). However, a portion of patients (16.5-25.8%) (10,11) were no longer suitable for radical surgery at the time of diagnosis due to the huge burden of PMP; for example, the massive disease invades the first porta hepatis or the caudate lobe, which is difficult to be cleaned, and the proximal third of the stomach and small bowel are involved, which would lead the length of the remnant intestines to be shorter than 2 m. For these patients, who represent a group with highly advanced PMP, the next best choice is debulking surgery (12). The definition of debulking surgery is a surgical technique that is done when the macroscopic tumor in the abdominal cavity cannot be removed.…”
Section: Introductionmentioning
confidence: 99%
“…Sugarbaker et al (8) first introduced complete cytoreductive surgery (CRS) plus heated intraoperative intraperitoneal chemotherapy (HIPEC), which provided new ideas for PMP treatment and has been suggested as the standard therapy (9). However, a portion of patients (16.5-25.8%) (10,11) were no longer suitable for radical surgery at the time of diagnosis due to the huge burden of PMP; for example, the massive disease invades the first porta hepatis or the caudate lobe, which is difficult to be cleaned, and the proximal third of the stomach and small bowel are involved, which would lead the length of the remnant intestines to be shorter than 2 m. For these patients, who represent a group with highly advanced PMP, the next best choice is debulking surgery (12). The definition of debulking surgery is a surgical technique that is done when the macroscopic tumor in the abdominal cavity cannot be removed.…”
Section: Introductionmentioning
confidence: 99%
“…PMP is seen in 9% of low-grade tumors, and it is reported that PMP develops in 67.9% of perforated mucinous neoplasms. CRS and hyperthermic intraperitoneal chemotherapy are also recommended for appendiceal neoplasms[ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates are high even when complete cytoreduction (CC‐0) can be achieved 9 . CRS‐HIPEC are major operations associated with significant postoperative morbidity, delaying the receipt of adjuvant chemotherapy when indicated 11 . For these reasons, the use of systemic chemotherapy before CRS‐HIPEC has long been of interest to investigators.…”
Section: Introductionmentioning
confidence: 99%